Extensión del límite austral de Persea lingue (Lauraceae) al sur de la Provincia de Palena, Región de los Lagos, Chile - Ezcurra, Cecilia (Gayana Botánica, 2010)
The finding of Persea lingue (Miers ex Bertero) Nees (Lauraceae) in the south of the province of Palena, Region X of Los Lagos, Chile, is reported. The new locality (Puerto Piedra: 43º 26’ S, 72º 09’ W) extends by some 250 km the southern limit previously described for the species in Chile. This is the first report of P. lingue from the North Patagonian rainforest. This species belonging to a mainly tropical genus had previously been associated with the warmer Valdivian, temperate-deciduous and sclerophyllous forests found in Chile further north.